Dagestiani woman in the system of physical culture and sport in 1930s: a historical aspect of the gender stereotypes transformation - Ganih Shikhvalievich Kaymarazov; Leyla Ganhievna Kaymarazova (Вестник Майкопского государственного технологического университета)
The relevance of the study is determined by the scientific and practical interest in the history of national physical culture and sports, the state policy in this area, including in the national regions of the country in the early Soviet period, as well as the discussions that have unfolded in the world community today about the fate of women’s sports. For the first time, the article analyzes the transformations that took place in the 1930s on the basis of reliable factual materials, taking into account modern historiographic generalizations in the structure of women’s gender role on the example of participation in the physical culture movement and sports of women of multinational Dagestan, which became more and more noticeable, despite the preservation of the significant influence of Islam and traditional ideas about the place of women in the system of social relations and the family. The research carried out within the framework of socio-cultural, gender history, the history of everyday life on the basis of the principles of historicism and objectivity with the use of comparative-historical, problem-chronological, descriptive methods and taking into account the main provisions of the modernization concept, led to the conclusion that in the 1930s ... the leadership of the republic and the region began to give priority attention to the involvement of mountain girls in the physical culture and military-sports movement, which became one of the components of the program for solving the "women’s issue", the implementation of which made it possible to more and more actively attract Dagestani women to participate in the socio-political and cultural life of the republic, edges, countries.